Voice acting for dummies - Ciccarelli, David; Ciccarelli, Stephanie (Mississauga, Ontario John Wiley and Sons Canada, Ltd., 2013)
Voice acting is a unique career, and this guide gives you expert tips and strategies on how to succeed. From finding your signature voice and creating a demo, to auditions and booking jobs, you'll learn how to improve your vocal talents and make a career out of them.
Introduction -- Exploring voice acting basics -- Creating your audio résumé -- Auditioning and finding work -- Setting up your voice acting business -- Establishing your home recording studio -- The part of tens.
"Learn to: get into character, create a demo, prepare for an audition, land your dream role."--Cover.
"Making everything easier."--Cover.
Includes index.
Keywords: Voice-overs.; Voice actors and actresses -- Vocational guidance